High‐intensity focused ultrasound: Safety and efficacy of a novel treatment modality for neurofibromatosis type 1 cutaneous neurofibroma - Sirkku Peltonen; Jørgen Serup; Mimmi Tang; Martin Gillstedt; Despoina Kantere; Noora Neittaanmäki; Peter Holmström; Jaishri O. Blakeley; Karli Rosner; Joshua Roberts; Torsten Bove; Katrine Elisabeth Karmisholt (Wiley, 2024)
Abstract Background High‐intensity focused ultrasound (HIFU) is widely used in the treatment of deep tumours, but clinical trials on skin tumours are not yet available. Neurofibromatosis Type I (NF1) is among the most common single‐gene inherited conditions worldwide and predisposes to benign and malignant neoplasms of the nervous system. Multiple cutaneous neurofibromas (cNFs) often cause social and functional limitations, itching and pain. Objectives The objective of this study was to investigate the safety, local tolerability and efficacy of a novel method utilizing HIFU for the treatment of cNFs. Methods A 20 MHz HIFU‐device with an integrated dermoscopic guidance and a handpiece with a focus depth of 2.3 mm below the skin surface was used. Doses of acoustic energy with 0.7 J/dose and pulse duration of 250 ms/dose were manually positioned with 1-2 mm distance between each applied dose. Number of applied doses depended on the size of the cNF. No anaesthetic was applied. Results Twenty patients with NF1 were recruited in two centres, and 147 cNFs were treated. There were no serious adverse events. Immediate and transient wheal‐and‐flare reactions occurred at treatment sites and occasionally there was minor epidermal damage which healed in 1-2 weeks. Dyspigmentation occurred in some tumours after 3-9 months but no scarring was observed at 9‐month follow‐up. During treatment, the patient‐reported pain‐score median was 3.5 (range 1-7) on a 0-10‐point scale. Clinical rating of cNFs after 9 months showed 48.9% full or major tumour reduction. The median reduction in tumour thickness measured by ultrasound at 9 months was 0.53 mm (range: -100% to +19%). Conclusions HIFU treatment is a new noninvasive, rapid and tolerable treatment modality that with high precision targets intradermal lesions. This study demonstrates acceptable safety, local tolerance and efficacy of HIFU for the treatment of cNFs that may further be developed also for other skin tumours.